RESPON POC URINE KELINCI TERHADAP PERTUMBUHAN DAN HASIL DUA VARIETAS TANAMAN BROKOLI (Brassica oleracea var. italic) - nanang khosim; Anis Sholihah; Siti Muslikah (AGRONISMA, 2020)
Broccoli is widely cultivated throughout the world, and thrives in areas with cold climates. Broccoli contains several vitamins including vitamins A, B1, B2, B5, B6 and E. And contains elements of Ca, Mg, Zn, and Fe and antioxidants. The study was conducted for 4 months, starting from May to September 2019. The research was carried out in the farmers' land of Jalan Tlogo Warna Block C, Tlogomas Village, Lowokwaru District, Malang. Altitude Â± 900 meters above sea level, average temperature of 240C. 2000-3000 rainfall / year. This research was conducted using a factorial randomized block design with first factor control: POC concentration in rabbit urine consisted of 3 levels, namely P1 = 50 ml / L POC rabbit urine, P2 = 100 ml / L POC rabbit urine, P3 = 150 ml / L POC rabbit urine. The second factor is the variety of broccoli seed varieties used consisting of 2 levels, namely V1 = Green Broccoli Varieties GREEN MAGIC, V2 = White Broccoli Varieties BIMA 45Of the two factors obtained 6 treatment combinations so that a total of 7 treatments plus control. Each treatment was repeated 3 times using 5 samples for each treatment. Treatment combination K = control, P1V1 = 50 ml / L POC rabbit urine green broccoli varieties GREEN MAGIC, P1V2 = 50 ml / L POC rabbit urine white rabbit varieties BIMA 45, P2V1 = 100ml / L POC urine rabbit varieties green broccoli GREEN MAGIC, P2V2 = 100ml / L POC rabbit urine white broccoli varieties BIMA 45, P3V1 150 ml / L POC rabbit urine green broccoli varieties GREEN MAGIC, P3V2 150 ml / L POC rabbit urine white broccoli varieties BIMA 45The results of research that has been carried out rabbit urine POC application is based on analysis of statistical data showing that the best concentration of rabbit urine POC is in the treatment application of rabbit urine POC 150 ml / l. Because the treatment is different from other treatments so that the POC of rabbit urine 150ml / l has higher nutrient content than the other concentrations.